PERBANDINGAN KOMPOSISI KIMIA MINYAK ATSIRI KULIT BUAH JERUK SUNDAI (CITRUS JHAMBIRI LUSH) SEGAR DAN KERING YANG DIPEROLEH SECARA DESTILASI - Lenny, Sovia (Jurnal Riset Kimia, 2007)
ABSTRACTEssential oils was isolated from peels sundai orange (Citrus jhambiri Lush) by destilation. Product was characterized by GC-MS. The product research show content essential oil of fresh peels are 1.260% and dried peels are 1.312%. Limonen content as major component of fresh peels are 58.49% and dried peels are 55.80%.Keyword : Citrus jhambiri Lush, essential oil, limonen